2011
DOI: 10.1103/physrevd.84.085021
|View full text |Cite
|
Sign up to set email alerts
|

AdS collapse of a scalar field in higher dimensions

Abstract: We point out that the weakly turbulent instability of anti-de Sitter space, recently found in [1] for four dimensional spherically symmetric Einstein-massless-scalar field equations with negative cosmological constant, is present in all dimensions d + 1 for d ≥ 3, contrary to a claim made in [2].

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
136
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(151 citation statements)
references
References 3 publications
14
136
0
1
Order By: Relevance
“…Concentration of energy on finer spatial scales leads to gravitational collapse (black hole formation is the analogue of the viscous cut-off for fluids). Later, this result was extended in a straightforward manner to higher dimensions d > 3 [5] and verified and generalized to more general models [6,7,8,9]. In particular, the existence of time-periodic solutions was shown in [8,9].…”
Section: Anti-de Sitter Spacetimementioning
confidence: 99%
See 2 more Smart Citations
“…Concentration of energy on finer spatial scales leads to gravitational collapse (black hole formation is the analogue of the viscous cut-off for fluids). Later, this result was extended in a straightforward manner to higher dimensions d > 3 [5] and verified and generalized to more general models [6,7,8,9]. In particular, the existence of time-periodic solutions was shown in [8,9].…”
Section: Anti-de Sitter Spacetimementioning
confidence: 99%
“…In [4,5] it was found that small perturbations of AdS d+1 for d ≥ 3 generically evolve into a black hole. This instability of AdS has been conjectured to be caused by the resonant transfer of energy to high frequencies.…”
Section: Description Of Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different aspects of scalar collapse in AdS d+1 have been studied in [15,[21][22][23][24][25][26]. We will focus here on how the time invested on the first bounce depends on the mass and thickness of the initial shell.…”
Section: Revival Timementioning
confidence: 99%
“…The minima of A m (t) correspond to the moments of maximal implosion of the matter shell and the maxima to its bounces against the AdS boundary, see figure 2. Following previous works [15,[21][22][23][24][25][26], we will consider a matter shell composed of a massless scalar field. The equations of motion for the system are [15] …”
Section: Jhep04(2015)038mentioning
confidence: 99%